2012
DOI: 10.2217/pgs.12.93
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide miRNA Expression Profiling of Human Lymphoblastoid Cell Lines Identifies Tentative SSRI Antidepressant Response Biomarkers

Abstract: The potential value of these miRNAs as tentative SSRI response biomarkers awaits validation with lymphocyte samples of major depression patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 59 publications
2
57
1
Order By: Relevance
“…For instance, one study demonstrated a relationship between escitalopram treatment with microRNA levels, revealing excess downregulation of miR-34c-5p and miR-770-5p (Bocchio-Chiavetto et al, 2013). Another antidepressant, paroxetine, increased miR-151-3p 6.7-fold in lymphoblastoid cell lines (Oved et al, 2012). In addition, rapidly growing and novel antidepressant, ketamine, decreased miR-451 levels as revealed by O' Connor Richard M et al, (2013).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, one study demonstrated a relationship between escitalopram treatment with microRNA levels, revealing excess downregulation of miR-34c-5p and miR-770-5p (Bocchio-Chiavetto et al, 2013). Another antidepressant, paroxetine, increased miR-151-3p 6.7-fold in lymphoblastoid cell lines (Oved et al, 2012). In addition, rapidly growing and novel antidepressant, ketamine, decreased miR-451 levels as revealed by O' Connor Richard M et al, (2013).…”
Section: Introductionmentioning
confidence: 95%
“…In this case, besides measuring its level in blood at baseline and longitudinally at different time points after psychotropic drug treatment, a patient's lymphocytes can be isolated and sensitivity of antidepressants can be tested in-vitro based on miR-124 expression profile. A similar approach has been discussed by Oved et al [17] where genome-wide miRNA expression profiling of human lymphoblastoid cell lines identified tentative antidepressant response biomarkers in humans. This approach may be highly useful in creating personalized medication for depressed patients which is currently lacking.…”
Section: Expert Opinionmentioning
confidence: 89%
“…Human, MDD Blood Escitalopram, 12 weeks ↑28 miRNAs including BDNF-related miR-132 ↓ miR-34c-5p and miR-770-5p Oved et al (2012) Human Cell line Paroxetine, 3 days Paroxetine sensitive cells had higher basal expression levels of miR-151-3p, associated with↓mRNA for miR-151-3p effector, CHL1, a neural cell adhesion molecule Basal levels of miR-212, mir-132, miR-30b*, let-7b and let-7c also differed significantly by more than 1.5 fold between the high and low sensitivity cell groups Rodrigues et al (2011) Human Cell lines…”
Section: Referencementioning
confidence: 99%